Optimization of Power Plant Operation Scheduling in Tahuna 1 Isolated System to Minimize the Levelized Cost of Electricity - Nugroho, Gilang Cahyo; Sambegoro, Poetro Lebdo (ITB Graduate School Conference, 2025)
The Tahuna 1 System consists of the Tahuna Diesel Power Plant, Tamako Diesel Power Plant, Sangihe Solar Power Plant, and Ulung Peliang Micro Hydro Power Plant which are synchronized through the 20 kV medium voltage network with a total net power capacity of 15,358 kW. The cumulative value of the Levelized Cost of Electricity (LCOE) of the Tahuna 1 System in 2023 reached Rp4,210.86/kWh. In this research, a scheme for hourly generating unit operation scheduling was designed on the Tahuna 1 System to minimize the LCOE by considering the system load profile, generating unit capacity, and spinning reserve. The design of the hourly operation scheduling scheme of generating units was carried out on 12 units of Tahuna Diesel Power Plant and 6 units of Tamako Diesel Power Plant as independent variables. Based on the results of the operation scheduling scheme with consideration of two spinning reserve units, there is a decrease in the LCOE value of the Tahuna 1 System from the initial Rp4,210.86/kWh to Rp2,913.66/kWh or 30.81% more economical compared to the current conditions. This scheduling scheme is also a better choice to implement when viewed from the operational reliability of the 20 kV distribution system.